Comparative changes in the rheological properties and cell wall metabolism in rind of healthy and creased fruit of Washington navel and navelina sweet orange ('Citrus sinensis' [L.] Osbeck) - Saleem, Basharat; Hassan, Imran; Singh, Zora; Malik, Aman; Pervez, Muhammad (Southern Cross Publishing, 2014)
Creasing is a physiological disorder in navel oranges and causes serious economic losses. In 2007, the comparative changes in rheological properties of the rind, levels of starch, phenolics, pectins and the activity of pectinesterase (PE) in albedo and flavedo tissues of the healthy and the creased fruit of ‘Washington Navel’ and ‘Navelina’ sweet orange at ripe stage were investigated. During 2009, dynamics of the activities of PE, exo and endo polygalacturonase (exo-PG, endo-PG), and endo-1, 4-ß -D-glucanase (EGase) enzymes in albedo and flavedo tissues of the healthy as well as the creased ‘Washington Navel’ sweet orange fruit at different maturation and ripening stages were researched. The rind hardness, stiffness and tensile force were substantially lower in the creased fruit than the healthy ones in ‘Washington Navel’ and ‘Navelina’. The levels of starch, total phenolics, total pectins and water insoluble pectins decreased in the albedo and flavedo of the creased than the healthy fruit in both the cultivars. The levels of water soluble pectins increased in the albedo and flavedo of the creased fruit when compared to the healthy ones in both the cultivars. The activities of PE in albedo and flavedo tissues were higher in the creased fruit when compared to the healthy fruit of ‘Washington Navel’ and ‘Navelina’ in 2007. The activities of PE, exo and endo PG and Endo-1, 4-ß -D-glucanase were higher in the albedo tissue of creased fruit of ‘Washington Navel’ orange at different fruit maturation and ripening stages.In conclusion, the higher activities of pectinesterase, exo- polygalacturonase, endo- polygalacturonase, and endo-1, 4-ß -D-glucanase in the albedo of creased fruit at commercial harvest seem to be associated with the enhanced loss of pectins and starch in the cell walls of albedo tissue, leading to cell wall loosening and cracks formation consequently reducing hardness, stiffness and tensile force of the rind.